Assessment of Clarias gariepinus as a biological control agent against mosquito larvae. Issue 1 (December 2016) - Chala, Buze; Erko, Berhanu; Animut, Abebe; Degarege, Abraham; Petros, Beyene
Abstract Background The emergence and spread of insecticide resistant mosquitoes renewed interest in investigating the use of larvivorous fish as a biological control agent. The potential ofClarias gariepinus fish in controllingAnopheles arabiensis and culicine larvae was assessed under laboratory and semi-field conditions. Results Small size (15–20 cm)C. gariepinus fish consumed greater number of mosquito larvae than the large size fish (25–40 cm) in the multivariate regression model (β = 13.36, 95 % CI = 4.57, 22.15). TheAnopheles larvae consumed was greater in number than the culicines larvae consumed by the fish (β = 12.10, 95 % CI = 3.31, 20.89). The number of larvae consumed was greater during the night hours than during the light hours (β = 30.06, 95 % CI = 21.27, 38.85). Amount of supplementary fish food did not cause significant differences in the number of mosquito larvae consumed by the fish among different groups.C. gariepinus was observed to feed on mosquito larvae under laboratory and semi-field conditions. Conclusion C. gariepinus fed on the larvae ofAn. arabiensis and culicines readily. Hence, it can be used as an alternative mosquito control agent in Ethiopia where the breeding habitats are small and localized.